2016
DOI: 10.1002/ajmg.b.32431
|View full text |Cite
|
Sign up to set email alerts
|

The contribution of protein intrinsic disorder to understand the role of genetic variants uncovered by autism spectrum disorders exome studies

Abstract: Several autism spectrum disorders (ASD) exome studies suggest that coding single nucleotide variants (SNVs) play an important role on ASD etiology. Usually, the pathogenic effect of missense mutations is estimated through predictors that lose accuracy for those SNVs placed in intrinsically disordered regions of protein. Here, we used bioinformatics tools to investigate the effect of mutations described in ASD published exome studies (549 mutations) in protein disorder, considering post-translational modificati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 86 publications
(81 reference statements)
0
9
1
Order By: Relevance
“…We recently showed that variants uncovered by ASD and SCZ exome studies placed in disordered regions may be harmful, affecting disorder properties and disorder related functional sites [Schuch et al, ]. However, our results from GWAS SNPs, did not show any of these adverse effects (Table ).…”
Section: Discussioncontrasting
confidence: 60%
See 3 more Smart Citations
“…We recently showed that variants uncovered by ASD and SCZ exome studies placed in disordered regions may be harmful, affecting disorder properties and disorder related functional sites [Schuch et al, ]. However, our results from GWAS SNPs, did not show any of these adverse effects (Table ).…”
Section: Discussioncontrasting
confidence: 60%
“…The present study also suggests the importance of including protein disorders when mutation functionality predictions are made. Although most of the known pathogenic mutations occurred in ordered regions [Vacic et al, ], the effects of mutations in disordered regions were underestimated [Schuch et al, ] and still need to be clarified. Psychiatric diseases present a high disorder content, which could be the target of pathogenic mutation, justifying the usage of intrinsic disorder properties.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…From an evolutionary point of view, the fate of a protein would then not only depend on the generation of partially-folded intermediates, but also from the equilibrium between "functional" or "potentially noxious" native conformers, which in turn might be determined by surface residues whose importance has been underestimated in classical biochemical and protein folding studies. In this regard, a growing number of reports underline that natural polymorphisms, including those related to IDRs, as key contributors to human diseases (38,39), and that single amino acid changes common in human population more likely affect binding interfaces with other proteins or nucleic acids (40).…”
Section: Discussionmentioning
confidence: 99%